Manajemen Pembelajaran Pendidikan Diniyyah Formal (PDF) Tingkat Wustho Pondok Pesantren Assalafi Al Fitrah Surabaya - Suroso Suroso (Adabiyah : Jurnal Pendidikan Islam, 2017)
Education Diniyah Formal PDF is the result of the modern development of madrasah diniyah in pesantren. PDF is a regeneration of madrasah diniyah system in non-formal pesantren to formal education system and a combination of religious science and general science. To improve the quality of PDF, there needs to be a planned management with clear objectives, in order to improve the quality of learning, it is necessary to have a learning management in accordance with the needs and abilities of students. In the implementation of learning includes planning, organizing, evaluation.The data collection used in this thesis is observation, interview and documentation. Acquisition of data is done by digging the source data from Head PDF Wustho, Waka curriculum, Assatidz and Santri. The subject of this research is the implementation of formal learning process diniyah. The purpose of this study to describe how the management of learning in PDF Wustho Pondok Pesantren Assalafi Al Fithrah Surabaya. This research is a qualitative descriptive study. From the results of this study it can be concluded that: Management of learning in PDF Pondok Pesantren Assalafi Al Fithrah has been done well with the existence of objective planning, material pelejaran, implementation of learning, time allocation and type of evaluation.Implementation of learning has been going well where in the learning process determined the allocation of time sesaui with the state of santri, materials and media used also adjust to the needs of santri. The obstacles faced from aspects of planning include infrastructure and media, implementation aspects include time and media allocation while on the aspect of assessment is the absence of relevant assessment structures. If the time allocation is added and the learning media is equipped the material will undoubtedly be easily digested by the students as a whole. Some problems related to this, need to be addressed immediately by turning the coaching program and curriculum development. Curriculum development is an effort to maintain and maintain the curriculum as it should be. Thus curriculum development is none other than to seek the implementation of the curriculum in accordance with the program and provisions that have been determined. And there needs to be a special allocation of infrastructure and funds for the procurement of RPP so that aspects of planning in management learning can take place maximum.